Systematic approach to the design of modular military housing units using six-sigma - Cho, B. H.; Kim, D. J.; Ha, T. (Scientia Iranica, 2019)
Military quarters and barracks are representative of housing units where the same plan is repeated and, thus, prefabricated housing production can be e ectively applied. These housing units are required to be disassembled and recycled as military forces are frequently reorganized and deployed to perform military actions. In order to meet these needs, this study proposes a systematic approach to the design of modular military housing units based on Six-Sigma concept. The application of Six-Sigma to modular military housing units allows customers' needs to be re ected on the critical-to-quality parameter, which summarizes the main design requirements. In addition, the design concept of the modular units can be developed based on the derived critical-to-quality functionalities. To evaluate the e ectiveness of the proposed approach, a representative example of military housing units is chosen and designed by utilizing the new modular units developed through this procedure. The weight of frames per unit area and factory manufacturing ratio of the new design are analyzed. The results of the comparison show that the use of the new modular units not only reduces construction cost signi cantly, but also greatly improves the quality of construction.
Keywords: Construction costs; Critical to qualities; Design concept; Housing production; Housing units; Military actions; Military force; Modular units; Military housing unit; Modular construction; Quality function deployment; Six-Sigma; Steel structure